PRESENCE OF CANDIDA ALBICANS IN HAWLEY PLATE WEARERS: A PILOT STUDY - Sorana Maria Bucur; Rozalia Popa; Dorin Ioan Cocoș; Aliz Beata Tunyogi; Petru Istrate (Romanian Society of Oral Rehabilitation, 2022)
to study the frequency of Candida albicans in Hawley plates' wearers compared to pediatric patients who do not wear orthodontic appliances. Material and method: we performed bacteriological examinations to highlight Candida in patients with and without Hawley plates. The study group consisted of 85 patients that were divided according two criteria: age and whether or not they wore Hawley plates. Statistical analysis was performed using the coefficient of determination R-squared. Results: The regression coefficient of 0.07 means there is no link between Candida albicans and age for patients with Hawley plates. The regression coefficient of 0.84 means that there is a fairly close correlation between the presence of Candida and patients who do not wear Hawley plates. We found a good correlation (0.75) between the presence of Candida albicans in the condition of the plaque wearing and how the situation would have been if the patients hadn't worn it. Conclusion: Hawley plates are predicting factors for Candida albicans, and in the case of wearers, the possibility of candidiasis increases with age.